Expert validation of a causal model of 21st-century academic leadership in northeastern Thailand - Dusadee Butburee; Nawee Udorn; Paitoon Puangyod (Institute of Advanced Engineering and Science, 2026)
This study aimed to validate and refine a causal model of factors influencing 21st-century academic leadership among secondary school administrators in northeastern Thailand. The study addresses the growing need for an integrative leadership framework that reflects digital transformation, instructional demands, and contextual constraints in contemporary educational reform. A qualitative expert validation design was employed. A total 10 experts in educational leadership, curriculum administration, and organizational development were purposively selected to participate in semi-structured in-depth interviews. Data were analyzed using thematic content analysis and cross-expert validation to ensure conceptual clarity and contextual relevance. The findings confirmed four interrelated causal domains: leadership personality and identity; contextual and organizational support systems; proactive instructional and curriculum leadership; and innovation-oriented professional learning culture. Instructional leadership emerged as a central mediating mechanism linking internal leadership capacity and external organizational conditions to academic leadership outcomes. A refined causal model with validated indicators was synthesized, providing a theoretically grounded foundation for future instrument development and structural equation modeling (SEM). The findings offer practical and policy implications for leadership development and sustainable school improvement in rapidly changing educational environments.